2020
DOI: 10.1109/access.2020.2986389
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on Arrhenius Equations and BP Neural Network Models to Predict Hot Deformation Behaviors of a Hypereutectoid Steel

Abstract: In order to predict the high-temperature deformation behavior of hypereutectoid steel, the hot compression tests were conducted in the strain rate range of (0.001∼1) s −1 and the deformation temperature range of (950∼1100) • C. The experimental data were employed to develop the Arrhenius constitutive model and BP neural network model, and their predictability for high temperature flow stress of hypereutectoid steel was further evaluated. Comparatively, a higher correlation coefficient (R) can be obtained for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Therefore, it is particularly suitable for modeling using artificial neural networks. Qiao et al [26] used Arrhenius model and BP neural network model to predict the high temperature deformation behavior of hypereutectoid steel and found that the model constructed by BP neural network has more accurate prediction results with higher correlation coefficient(R) and mean absolute relative error (AARE). In their investigation of the superplastic forming of Ti-2.5Al-1.8Mn, Mosleh A et al [27] used an Arrhenius-type model and an artificial neural network model to describe the behavior at high temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is particularly suitable for modeling using artificial neural networks. Qiao et al [26] used Arrhenius model and BP neural network model to predict the high temperature deformation behavior of hypereutectoid steel and found that the model constructed by BP neural network has more accurate prediction results with higher correlation coefficient(R) and mean absolute relative error (AARE). In their investigation of the superplastic forming of Ti-2.5Al-1.8Mn, Mosleh A et al [27] used an Arrhenius-type model and an artificial neural network model to describe the behavior at high temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the artificial neural network model has a large parallel processing structure, which can be used to depict the complex flow behavior of materials through a variety of nonlinear relationships. [ 36–42 ]…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Due to its prominent performance in antiwearing and high strength, eutectoid or hypereutectoid steels with nearly fully pearlitic microstructure have been viewed as candidate materials for heavy-haul railway applications. [5] However, the heavier transport conditions tend to significantly increase the risk of damage and failure of rail steels. [6][7][8][9][10] Serving in complicated conditions, it is generally acceptable that the rails life is strongly related to the wear behavior, including the abrasive, adhesive, and wear mechanisms.…”
Section: Introductionmentioning
confidence: 99%